2020
DOI: 10.31635/ccschem.020.202000146
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Difluorocarbene Involved Catalytic Coupling with Terminal Alkynes

Abstract: Cite this: CCS Chem. 2020, 2, 293-304Difluoromethylated alkynes are a versatile synthon for the diversity-oriented synthesis of difluoromethyl compounds that are of great interest in life and materials sciences. However, the catalytic cross-coupling for the synthesis of difluoromethylated alkynes remains challenging, despite impressive achievements made in the cross-coupling reactions for alkynes, including the Sonogashira reaction. Here, we report a palladium difluorocarbene involvement in catalytic coupling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 31 publications
0
25
0
1
Order By: Relevance
“…In 2020, Zhang and co-workers extended the palladium difluorocarbene ([Pd = CF 2 ]) chemistry (described in Section 2.1.c) to the difluoromethylation of alkynes (Scheme 63). 206 The protocol employed chlorodifluoromethane as the difluorocarbene precursor, and featured good functional group tolerance, broad substrate scope, and was applied to the synthesis of complex drug molecules. One limitation of this method is the use of chlorodifluoromethane, an ODS.…”
Section: Difluoromethylation Of Alkynesmentioning
confidence: 99%
“…In 2020, Zhang and co-workers extended the palladium difluorocarbene ([Pd = CF 2 ]) chemistry (described in Section 2.1.c) to the difluoromethylation of alkynes (Scheme 63). 206 The protocol employed chlorodifluoromethane as the difluorocarbene precursor, and featured good functional group tolerance, broad substrate scope, and was applied to the synthesis of complex drug molecules. One limitation of this method is the use of chlorodifluoromethane, an ODS.…”
Section: Difluoromethylation Of Alkynesmentioning
confidence: 99%
“…The transformation of difluorocarbene (:CF 2 ) has emerged as a powerful difluorination platform, which can be widely used to introduce fluorine into organic molecules. [1][2][3][4] Typical conversion of difluorocarbene, including attachment with a nucleophile and an electrophile, [5][6][7][8][9][10][11][12][13][14][15][16] Wittig reaction with carbonyls, [17][18][19][20] [2+1] cycloaddition with alkenes or alkynes 21 , metal-difluorocarbene involved catalytic coupling [22][23][24] and combining with other carbene, [25][26][27][28][29] can quickly construct different organofluorine compounds, such as gemdifluoroalkenes and gem-difluorocyclopropanes and other gem-difluorinated compounds (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Ngai et al reported a distinct radical approach for catalytic C-H difluoromethoxylation of (hetero)arenes using difluoromethoxylative reagents [11][12] (Figure 1B, left). Of note, as an important and special fluorine-containing intermediate in organic synthesis [13][14][15][16][17][18][19][20][21][22][23][24] , difluorocarbene has been combined with various alcohols or thiolsto synthesize difluoromethyl ethers [25][26][27][28] or thioethers [29][30] (Figure 1B, right). Despite the progress achieved in recent years on the synthesis of difluoromethyl ethers, their efficient synthetic methods are still rare and the development of a general and practical strategy for their construction is still highly appealing, especially in terms of complexity and versatility of difluoromethoxy compounds.…”
Section: Introductionmentioning
confidence: 99%